Visitor Restrictions, Palliative Care, and Epistemic Agency: A Qualitative Study of Nurses' Relational Practice During the Coronavirus Pandemic - Kim McMillan; David Kenneth Wright; Christine J. McPherson; Kristina Ma; Vasiliki Bitzas (SAGE Publishing, 2021)
Efforts to curb spread of COVID-19 has led to restrictive visitor policies in healthcare, which disrupt social connection between patients and their families at end of life. We interviewed 17 Canadian nurses providing palliative care, to solicit their descriptions of, and responses to, ethical issues experienced as a result of COVID-19 related circumstances. Our analysis was inductive and scaffolded on notions of nurses' moral agency, palliative care values, and our clinical practice in end-of-life care. Our findings reveal that while participants appreciated the need for pandemic measures, they found blanket policies separating patients and families to be antithetical to their philosophy of palliative care. In navigating this tension, nurses drew on the foundational values of their practice, engaging in ethical reasoning and action to integrate safety and humanity into their work. These findings underscore the epistemic agency of nurses and highlight the limits of a purely biomedical logic for guiding the nursing ethics of the pandemic response.